PERANCANGAN VIDEO TESTIMONI MIRACLE MALE AESTHETIC TREATMENT - Deli Deli; Michael Jonathan (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Based on products produced for sale to the public, the experience felt by users or product connoisseurs has an impression on the products consumed in improving the image of the company itself, therefore video testimonials are one way to be able to provide a positive perspective on the company and with the hope that it can provide a sentiment that can support the trust of customers or product users to the wider community, especially for those who have never used the product in order to get an overview or benefit that will be obtained from using the product. Solving the problems faced in this study using the Multimedia Development Life Cycle (MDLC) method, namely by staying focused on the six stages of problem solving in product development. Videos are packaged and distributed through social media platforms such as Instagram to attract new potential customers in this modern era with the hope that the products offered by the company can be better known by the wider community.